Myocardial infarction in the absence of obstructive coronary artery disease - can the underlying causes be identified by cardiac magnetic resonance?. (13th July 2021) - Martins De Carvalho, M; Pinto, RA; Proenca, T; Grilo, P; Resende, CX; Amador, AF; Costa, CM; Calvao, J; Torres, S; Cabrita, A; Marques, C; Vasconcelos, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Myocardial Infarction in the Absence of Obstructive Coronary Artery Disease (MINOCA) is a clinical entity that occurs in up to 15% of all acute coronary syndromes (ACS). It is a "working diagnosis", as it is constituted by several etiologies. Purpose: To identify the utility of CMR in determining the etiological diagnosis of MINOCA events, with potential impact in the therapeutic management of these patients. Methods: Patients with MINOCA who were admitted to the Cardiology department at a tertiary center, between 2015 and 2020, were included. MINOCA was defined as an ACS with non-obstructive (<50%) coronary artery disease and no other clinically specific cause, in accordance with definition adopted in the 2020 ESC Guidelines for the management of ACS in patients presenting without persistent ST-segment elevation. Patients who did not had a coronary exam (either CT or invasive angiogram) or a CMR were excluded. All CMR exams were performed in a 3 Tesla equipment using a comprehensive protocol (cine, T2-weighted, and late gadolinium sequences). Clinical, electrocardiographic, echocardiographic and CMR data were collected. Results: In a population of 29 patients, the mean age was 55 ± 17 years-old at the time of the cardiac event, 51.7% were male. Concerning to cardiovascular risk factors, 58.6% of patients had dyslipidaemia, 51.7% had hypertension, 13.7% were diabetic, 41.4% were smokers or previous smokers and 31.0% had obesity. Atrial fibrillation was present in 3.4% of patients. As for the EKG patterns, 41.4% of the patients had ventricular repolarization changes, 13.8% had a transitory ST elevation pattern, 6.9% had a complete left bundle branch block and 37.9% had a normal EKG; most of the ischemic EKG alterations were on the anterior wall (66.7%). The median high sensitivity I troponin levels were 1877.5 (IQR 225.3 – 5985.8) ng/L. The majority of patients (58.6%) had echocardiographic wall motion abnormalities; of those, the most common (41.1%) were on the left anterior descendent artery territory. CMR (performed at a median of 5 days from presentation) was able to identify the cause for the troponin rise in 58.6% of the cases; late gadolinium enhancement and oedema were present in 41.4% and 62.1% of patients, respectively. The mean left ventricle ejection fraction (EF) was 57.7 ± 8.5% and the mean right ventricle EF was 61.5 ± 6.1%. An ischemic pattern was present in 29.4% of the total population. In 17.6% of the patients findings were consistent with Takotsubo syndrome and in 29.4% with myocarditis. Conclusion: CMR established the etiological cause in 58.6% of the cases, with potential implications in medical therapy. These findings highlight the importance of CMR in MINOCA diagnosis and the potential improvement in patient care with multi-modality imaging.